2020
DOI: 10.1101/2020.03.26.009829
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of a candidate vaccine on the dynamics of salmon lice (Lepeophtheirus salmonis) infestation and immune response in Atlantic salmon (Salmo salarL.)

Abstract: Title): Effectiveness of fusion peptide-based vaccine TT-P0 on the dynamics of salmon lice 2 (Lepeophtheirus salmonis) infection in Atlantic salmon (Salmo salar L.) 3 4 (Short title): TT-P0 vaccine and salmon lice infection 5 6 (Authors): Abstract 24 Infection with parasitic copepod salmon louse Lepeophtheirus salmonis, represents one of the most 25 important limitations to sustainable Atlantic salmon (Salmo salar L.) farming today in the North 26 Atlantic region. The parasite exerts negative impact on health,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Sequencing of homologous or conserved genes based on proteins and vaccine targets of ticks and other arthropods has proven an effective approach in antigen mining for sea lice. [615][616][617] RNAi enables functional characterisation of vaccine candidates 624 and has been applied to characterise a number of potential sea lice vaccine candidates including biomolecules involved in egg production (e.g., yolk-associated protein;…”
Section: Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequencing of homologous or conserved genes based on proteins and vaccine targets of ticks and other arthropods has proven an effective approach in antigen mining for sea lice. [615][616][617] RNAi enables functional characterisation of vaccine candidates 624 and has been applied to characterise a number of potential sea lice vaccine candidates including biomolecules involved in egg production (e.g., yolk-associated protein;…”
Section: Vaccinesmentioning
confidence: 99%
“…Sequencing of homologous or conserved genes based on proteins and vaccine targets of ticks and other arthropods has proven an effective approach in antigen mining for sea lice 615–617 . RNAi enables functional characterisation of vaccine candidates 624 and has been applied to characterise a number of potential sea lice vaccine candidates including biomolecules involved in egg production (e.g., yolk‐associated protein; LsYAP, 625 ), digestion (e.g., KEDL receptor; LsKDELR and vesicular coatomer protein complex; LsCOPB2, 626 ), muscle activity (e.g., LsalMS, 627 ) and immunomodulation (e.g., prostaglandin E‐synthase 2; PGES2, 628 ) leading to impaired parasite reproductive capacity, digestion and development.…”
Section: Technologies and Approaches For Boosting Host Resistancementioning
confidence: 99%
“…Further, a number of proteins have also been evaluated against sea lice with varying successes, for example, a novel gene (denoted as my32) from C rogercresseyi that showed the highest identity with the L salmonis gene akirin-2; 55 putative Toll-like receptor 6 and, potassium chloride and amino acid transporter from midgut function and blood digestion of L salmonis, 10 and a peptide from ribosomal P0 protein of L salmonis fused with T-cell epitopes. 56 The new antigens reported here add to this repertoire of proteins already been suggested as vaccine candidates in fish lice/sea lice. However, further studies need to be carried out to determine the sites of expression of these proteins in A siamensis by immunolocalization.…”
Section: Discussionmentioning
confidence: 86%
“…Another recombinant vaccine targeting the vitellogenin in the parasite resulted in lower number of attached female lice and less erosion or wounds on the vaccinated sh compared to the unvaccinated control (Frost et al, 2007). Furthermore, vaccines developed using a recombinant peptide from the ribosomal protein P0 resulted in reduction in attached female lice and their ability to produce eggstrings that supposedly continued into the F1 lice generation (Swain et al, 2020). A recent study showed that a recombinant lice gut protein named P33, elicited speci c antibodies after immunization and resulted in reduction of immature and adult stages of salmon lice (Tartor et al, 2021).…”
Section: Introductionmentioning
confidence: 99%